Analisis Perbandingan Realisasi Anggaran BPHTB Periode (2020-2024) Terhadap Peningkatan Pendapatan Asli Daerah Kota Medan - Ananda, Iqbal; Rosalina, Melissa; Rahmansyah, Riki (Jaanur Elbarik Indonesia, 2025)
This study aims to examine the discrepancy between the targeted figures and the actual achievement of Land and Building Acquisition Tax (BPHTB) revenue in the Medan City area during the period 2020 to 2024. Quantitative methods include descriptive analysis, comparative techniques, and simple linear regression on secondary data from the local Regional Revenue Agency (BAPENDA). The results of the study indicate that the realization of BPHTB has a significant impact on the growth of PAD, with a peak achievement of 95.59% occurring in 2021 and a low point of 62.84% in 2023. Although the average value tends to increase, the data shows a high level of variation and extreme distribution. The results of statistical tests show a very close positive linear relationship between the realization of BPHTB and PAD (indicated by a correlation coefficient reaching 0.971), however, its statistical significance is limited due to the relatively small number of samples and quite sharp data fluctuations. Among the inhibiting factors identified are the still low level of understanding and concern of taxpayers, inadequate levels of compliance, and socialization and supervision from local governments that have not been running optimally